2017
DOI: 10.3389/fcimb.2017.00331
|View full text |Cite
|
Sign up to set email alerts
|

The feoABC Locus of Yersinia pestis Likely Has Two Promoters Causing Unique Iron Regulation

Abstract: The FeoABC ferrous transporter is a wide-spread bacterial system. While the feoABC locus is regulated by a number of factors in the bacteria studied, we have previously found that regulation of feoABC in Yersinia pestis appears to be unique. None of the non-iron responsive transcriptional regulators that control expression of feoABC in other bacteria do so in Y. pestis. Another unique factor is the iron and Fur regulation of the Y. pestis feoABC locus occurs during microaerobic but not aerobic growth. Here we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 39 publications
(79 reference statements)
0
9
0
Order By: Relevance
“…RT-qPCR data show that all three studied genes are repressed by Fur in Y. enterocolitica cells grown aerobically, which is in agreement with the results of studies in E. coli [ 18 , 127 , 128 , 129 ]. Interestingly, a recent study on the transcriptional activity of feoABC in Y. pestis revealed that Fur-mediated regulation of this locus occurs during microaerobic but not aerobic growth [ 20 ]. The most obvious transcriptional change (repression by Fur) was observed for the fepA gene encoding the FepA receptor for ferric enterobactin, the most potent siderophore of E. coli [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT-qPCR data show that all three studied genes are repressed by Fur in Y. enterocolitica cells grown aerobically, which is in agreement with the results of studies in E. coli [ 18 , 127 , 128 , 129 ]. Interestingly, a recent study on the transcriptional activity of feoABC in Y. pestis revealed that Fur-mediated regulation of this locus occurs during microaerobic but not aerobic growth [ 20 ]. The most obvious transcriptional change (repression by Fur) was observed for the fepA gene encoding the FepA receptor for ferric enterobactin, the most potent siderophore of E. coli [ 130 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferrous iron is thought to diffuse freely through the OM porins into the periplasm from where it is transported into the cytoplasm via the FeoABC system [ 19 ]. Systems homologous to FeoABC have been identified in pathogenic Yersinia species [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Besides the siderophores, ferrous-iron transporters including yptb3767 ( feoA) were essential to Y. pseudotuberculosis but not to Y. pestis . During aerobic growth of Y. pestis , both ferric and ferrous iron uptake systems are generally repressed by the Fe- fur regulon; the exception being the feo system, which is repressed in the presence of iron only in microaerophilic conditions [ 79 ]. Feo may therefore be expected to be equally important to Y. pestis as to Y. pseudotuberculosis during iron-replete aerobic growth, but its mutation is known to be compensated for by the yfe system.…”
Section: Discussionmentioning
confidence: 99%
“…The Yfu and Yiu systems are ABC transporters that play a role in ferric iron uptake under aerobic conditions, while the Feo and Fet systems can uptake ferrous iron under microaerophilic conditions (Perry et al, 2015 ). Recently, work has shown that the Feo system can also uptake ferric iron (O'Connor et al, 2017 ). The Yfe system has been shown to play a role in both ferric and ferrous iron transport under aerobic and microaerophillic conditions, respectively (Perry et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%